Effect of Irradiation Distance of LED on Bulk-Fill Composite Resin Hardness - Badi Soerachman; Annisa Trifani Nur Fadhillah; Atia Nurul Sidiqa; Hartanto Endrowahyudi (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Bulk-fill composite is a restorative material with the advantage of 4 mm thickness application into the cavity and good modulus of elasticity similar to natural teeth. One of the important aspect in composite restoration is polymerization which is a formation of polymer from monomers. One way to achieve a high degree of polymerization is to use Light Emitting Diode (LED) irradiation, which will increase the hardness of the composite resin. Objective: The purpose of this study was to determine the effect of distance between the LED tip with bulk-fill composite surface on the hardness of composite. Methods: Fifteen samples were divided into three groups with irradiation distance of 0 mm, 5 mm, and 9 mm respectively. Samples were made in a cylindrical shape with 6 mm of diameter and 4 mm of height then irradiated with LED for 10 seconds. The samples then immersed in distilled water at 37o for 24 hours. Hardness test was carried out on three different points at the top and bottom each side using Vickers hardness test. Data was analyzed with Shapiro-Wilk and One Way ANOVA. Results: The highest hardness value was obtained in the group with an irradiation distance of 0 mm, while the lowest was in the group with irradiation distance of 9cm, both on the top and bottom surfaces. Increasing the distance between the tip of light curing unit and the composite surface resulted in a significant reduction in the hardness of the composite. Conclusion: There were significant differences in the hardness value of bulk-fill composite in all distance group.